Design and Testing of Efficient Mucus‐Penetrating Nanogels—Pitfalls of Preclinical Testing and Lessons Learned. Issue 23 (14th March 2021) - Charbaji, Rawan; Kar, Mrityunjoy; Theune, Loryn E.; Bergueiro, Julián; Eichhorst, Anne; Navarro, Lucila; Graff, Patrick; Stumpff, Friederike; Calderón, Marcelo; Hedtrich, Sarah
Abstract: Mucosal surfaces pose a challenging environment for efficient drug delivery. Various delivery strategies such as nanoparticles have been employed so far; yet, still yielding limited success. To address the need of efficient transmucosal drug delivery, this report presents the synthesis of novel disulfide‐containing dendritic polyglycerol (dPG)‐based nanogels and their preclinical testing. A bifunctional disulfide‐containing linker is coupled to dPG to act as a macromolecular crosslinker for poly‐ N ‐isopropylacrylamide (PNIPAM) and poly‐ N ‐isopropylmethacrylamide (PNIPMAM) in a precipitation polymerization process. A systematic analysis of the polymerization reveals the importance of a careful polymer choice to yield mucus‐degradable nanogels with diameters between 100 and 200 nm, low polydispersity, and intact disulfide linkers. Absorption studies in porcine intestinal tissue and human bronchial epithelial models demonstrate that disulfide‐containing nanogels are highly efficient in overcoming mucosal barriers. The nanogels efficiently degrade and deliver the anti‐inflammatory biomacromolecule etanercept into epithelial tissues yielding local anti‐inflammatory effects. Over the course of this work, several problems are encountered due to a limited availability of valid test systems for mucosal drug‐delivery systems. Hence, this study also emphasizes how critical a combined and multifaceted approach is for the preclinical testing of mucosal drug‐delivery systems, discusses potential pitfalls, and provides suggestions for solutions. Abstract : Novel disulfide‐containing dendritic polyglycerol‐based nanogels act as highly efficient transmucosal drug delivery systems. Upon encountering the mucus layer, they undergo gradual redox‐dependent degradation, and thus are able to penetrate the mucous barrier and achieve efficient intraepithelial drug delivery of encapsulated therapeutics (e.g., etanercept). Here, comprehensive, and multifaceted approaches are implemented to overcome distinct pitfalls and shortcomings of current mucous test systems.